2021
DOI: 10.1038/s41598-020-79616-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the unimodal size scaling of phytoplankton growth

Abstract: Contrary to predictions by the allometric theory, there is evidence that phytoplankton growth rates peak at intermediate cell sizes. However, it is still unknown if this pattern may result from the effect of experimental temperature. Here we test whether temperature affects the unimodal size scaling pattern of phytoplankton growth by (1) growing Synechococcus sp., Ostreococcus tauri, Micromonas commoda and Pavlova lutheri at 18 °C and 25 °C, and (2) using thermal response curves available in the literature to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…An enhanced biomass contribution by small nanophytoplankton as a result of experimental nutrient enrichment also agrees with the large-scale patterns identified in the Atlantic Ocean, whereby nanophytoplankton biomass contribution increases from oligotrophic to mesotrophic regions 80,81 . Within the picophytoplankton, picoeukaryotes (2-3 µm in cell diameter) are more responsive to nutrient enrichment than picocyanobacteria (0.5-1.5 µm) 39,42 , a pattern related to the positive relationship between cell size and maximum growth rates observed for cells < 5 µm 37,79,82 . Conversely, Prochlorococcus has a streamlined genome and reduced nutrient requirements 83 that make it particularly well-adapted to ultraoligotrophic conditions but tends to be outcompeted by larger, faster-growing species when nutrient limitation is relieved, in addition to suffering stronger losses to grazing 28,84 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An enhanced biomass contribution by small nanophytoplankton as a result of experimental nutrient enrichment also agrees with the large-scale patterns identified in the Atlantic Ocean, whereby nanophytoplankton biomass contribution increases from oligotrophic to mesotrophic regions 80,81 . Within the picophytoplankton, picoeukaryotes (2-3 µm in cell diameter) are more responsive to nutrient enrichment than picocyanobacteria (0.5-1.5 µm) 39,42 , a pattern related to the positive relationship between cell size and maximum growth rates observed for cells < 5 µm 37,79,82 . Conversely, Prochlorococcus has a streamlined genome and reduced nutrient requirements 83 that make it particularly well-adapted to ultraoligotrophic conditions but tends to be outcompeted by larger, faster-growing species when nutrient limitation is relieved, in addition to suffering stronger losses to grazing 28,84 .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, our estimates of the biomass contribution by different size classes indicated that, although picophytoplankton carbon did increase in response to added nutrients, the response of the small nanophytoplankton was stronger, because their contribution to total carbon consistently increased in nutrient-enriched treatments. Thus it seems that most of the net biomass increase after nutrient addition was due to small nanophytoplankton cells, which have been shown to have faster maximum growth rates than their smaller counterparts 37,79 . An enhanced biomass contribution by small nanophytoplankton as a result of experimental nutrient enrichment also agrees with the large-scale patterns identified in the Atlantic Ocean, whereby nanophytoplankton biomass contribution increases from oligotrophic to mesotrophic regions 80,81 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cell size, warming to 9 °C resulted in a relative increase in intermediate (2–20 µm) as well as a reduction of large (20–150 µm) and small (0.8–2 µm) eukaryotes ( Figure 3 a and Figure S3 ). Other studies have also found intermediate-sized organisms to exhibit higher growth rates compared to smaller and larger ones with increasing temperatures [ 10 ]. While this is generally in line with the theory of unimodal size scaling of planktonic growth [ 13 ], it contrasts predictions from the allometric theory of cell size decreasing with temperature [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, trait differences among competing species have been identified as a good predictor for planktonic reorganization [ 9 ]. With regard to warming, traits such as the cell size [ 10 ] and the trophic mode [ 11 ] are known to affect the fitness and performance of a species, as they influence the thermal reaction norm for maximum growth [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation